Peran Notaris dalam Menjamin Keabsahan dan Autentisitas Akta Kredit Perbankan - Pyarrani, Dilla; Burhanuddin, Sisca Ferawati (Universitas Semarang, 2025)
This study examines the role of notaries in ensuring the validity and authenticity of authentic deeds in banking credit agreements and analyzes the legal implications of the degradation of their evidentiary value. In banking practice, credit agreements are commonly executed in the form of authentic deeds to guarantee legal certainty and provide conclusive evidence in dispute resolution. However, in judicial proceedings, the evidentiary strength of authentic deeds may be challenged and reduced through counter-evidence, particularly when material or formal defects are proven. This condition raises concerns regarding public trust in notarial deeds and the notarial profession. This research employs a normative juridical method with a statutory and conceptual approach, relying on secondary legal materials obtained through library research. The findings indicate that the evidentiary perfection of authentic deeds depends on a dual responsibility inherent in their classification as partij acte. Notaries are responsible for ensuring formal authenticity through compliance with statutory procedures and the principle of due diligence, while the parties bear responsibility for material validity through good faith in providing accurate information and supporting documents. Failure to fulfill these requirements may result in the degradation of the deed’s evidentiary value, either rendering it void, voidable, or reducing it to a private deed. This study contributes by clarifying the distribution of legal responsibility between notaries and the parties and emphasizes the importance of professional ethics, good faith, and procedural compliance to maintain legal certainty and public confidence in authentic deeds within banking transactions. Penelitian ini mengkaji peran Notaris dalam menjamin keabsahan dan autentisitas akta autentik perjanjian kredit perbankan serta menganalisis implikasi hukum dari degradasi nilai pembuktiannya. Dalam praktik perbankan, perjanjian kredit umumnya dibuat dalam bentuk akta autentik guna menjamin kepastian hukum dan menyediakan alat bukti yang sempurna dalam penyelesaian sengketa. Namun, dalam proses peradilan, kekuatan pembuktian akta autentik dapat dipatahkan melalui pembuktian sebaliknya apabila terbukti terdapat cacat formil maupun materiil. Kondisi tersebut berpotensi memengaruhi kepercayaan publik terhadap akta autentik dan profesi Notaris. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan perundang-undangan dan konseptual, berdasarkan studi kepustakaan terhadap bahan hukum sekunder. Hasil penelitian menunjukkan bahwa kesempurnaan nilai pembuktian akta autentik ditentukan oleh pembagian tanggung jawab yang melekat pada sifatnya sebagai partij acte. Notaris bertanggung jawab menjamin autentisitas akta melalui ketaatan prosedural dan asas kehati-hatian, sedangkan para pihak bertanggung jawab atas keabsahan materiil melalui penerapan asas itikad baik dalam pemberian keterangan dan dokumen pendukung. Ketidakpatuhan terhadap unsur-unsur tersebut dapat mengakibatkan degradasi nilai pembuktian akta, baik menjadi batal demi hukum, dapat dibatalkan, maupun tereduksi menjadi akta di bawah tangan. Penelitian ini menegaskan pentingnya profesionalitas Notaris, kejujuran para pihak, dan kepatuhan prosedural guna menjaga kepastian hukum serta kepercayaan publik dalam transaksi kredit perbankan.